A Collective Effort to Improve Sociology Students' Writing Skills. (April 2014) - Burgess-Proctor, Amanda; Cassano, Graham; Condron, Dennis J.; Lyons, Heidi A.; Sanders, George
Nationwide, academic sociologists at all types of higher education institutions face the challenge of working to improve students' writing skills. In this article, we describe a collective effort by a group of faculty members in one undergraduate sociology program to implement several effective writing-improvement strategies. We advocate aiming to improve students' writing by working together on a united front rather than working in isolation. After explaining the origins of the collective emphasis on writing that emerged in our group and briefly outlining the writing-improvement strategies that we utilize, we use student survey data to reflect on major themes before concluding with a discussion of the merits of our collective approach.